Negative interaction between emotional vulnerability and depressive symptoms may heighten suicidal ideation among Japanese university students: a cross-sectional study - Yamaguchi, Shinji; Nagamine, Daiki; Murofushi, Yuka; Matsuda, Kojiro (Frontiers in Psychiatry, 2024)
Introduction: Studies examining the relationships among suicidal ideation, emotional vulnerability, and depressive symptoms are scarce. This study examined the effects of emotional vulnerability and depressive symptoms on suicidal ideation among Japanese university students. Methods: A questionnaire survey was conducted with 370 Japanese university students. Data were analyzed using descriptive statistics and multiple regression analysis. Results: In the multiple regression analysis, depressive symptoms were significant (β = .46, p < .001) but emotional vulnerability was not (β = .05, p = .318). A significant interaction emerged between emotional vulnerability and depressive symptoms (β = .22, p < .001). The model's R 2 value was .31 (p < .001). Simple slopes tests revealed the impact of depressive symptoms on suicidal ideation, even with low emotional vulnerability (b = .06, β = .27, p < .001), and a higher impact with high emotional vulnerability (b = .15, β = .65, p < .001). Discussion: The negative interaction between emotional vulnerability and depressive symptoms may heighten suicidal ideation among Japanese university students. Interventions targeting emotional vulnerability may help reduce suicidal ideation and achieve lower suicide rates.